Factors predicting dysphagia after anterior cervical surgery: A multicenter retrospective study for 2 years of follow-up. Issue 34 (August 2017) - Wang, Tao; Ma, Lei; Yang, Da-Long; Wang, Hui; Bai, Zhi-Long; Zhang, Li-Jun; Ding, Wen-Yuan
Abstract : Abstract: A multicenter retrospective study. The purpose of this study was to explore risk factors of dysphagia after anterior cervical surgery and factors affecting rehabilitation of dysphagia 2 years after surgery. Patients who underwent anterior cervical surgery at 3 centers from January 2010 to January 2013 were included. The possible factors included 3 aspects: demographic variables—age, sex, body mass index (BMI): hypertension, diabetes, heart disease, smoking, alcohol use, diagnose (cervical spondylotic myelopathy or ossification of posterior longitudinal ligament), preoperative visual analogue scale (VAS), Oswestry Disability Index (ODI), Japanese Orthopaedic Association (JOA), surgical-related variables—surgical option (ACDF, ACCF, ACCDF, or Zero profile), operation time, blood loss, operative level, superior fusion segment, incision length, angle of C2 to C7, height of C2 to C7, cervical circumference, cervical circumference/height of C2 to C7. The results of our study indicated that the rate of dysphagia at 0, 3, 6, 12, and 24 months after surgery was 20%, 5.4%, 2.4%, 1.1%, and 0.4%, respectively. Our results showed that age (58.8 years old), BMI (27.3 kg/m 2 ), course of disease (11.6 months), operation time (103.2 min), blood loss (151.6 mL), incision length (9.1 cm), cervical circumference (46.8 cm), angle of C2 to C7 (15.3°), cervical circumference/height of C2 to C7 (4.8), preoperative VAS (7.5), and ODI (0.6) in dysphagia group were significantly higher than those (52.0, 24.6, 8.6, 88.2, 121.6, 8.6, 42.3, 12.6, 3.7, 5.6, and 0.4, respectively) in nondysphagia group; however, height of C2 to C7 (9.9 vs 11.7 cm) and preoperative JOA (8.3 vs 10.7) had opposite trend between 2 groups. We could also infer that female, smoking, diabetes, ossification of posterior longitudinal ligament, ACCDF, multilevel surgery, and superior fusion segment including C2 to C3 or C6 to C7 were the risk factors for dysphagia after surgery immediately. However, till 2 years after surgery, only 2 risk factors, smoking and diabetes, could slow rehabilitation of dysphagia. Many factors could significantly increase rate of dysphagia after anterior cervical surgery. Operation time as a vital factor markedly increases immediate postoperative dysphagia and smoking, as the most important factor, lower recovery of dysphagia. Further study is needed to prove if these factors could influence dysphagia.